Talent Development in European Higher Education : Honors programs in the Benelux, Nordic and German-speaking countries - Wolfensberger, Dr. Marca V.C (Springer International Publishing : Imprint: Springer, 2015)
This book examines the much-debated question of how to unleash the potential of young people with promising intellectual abilities and motivation. It looks at the increasingly important topic of excellence in education, and the shift in focus towards the provision of programs to support talented students in higher education. It provides a systematic overview of programs for talented students at northern European higher education institutions (HEIs). Starting in the Netherlands, where nearly all HEIs have developed honors programs over the past two decades, the book explores three clusters of countries: the Benelux, the Nordic and the German-speaking countries. For each of these countries, it discusses the local culture towards excellence, the structure of the education system, and the presence of honors programs. In total, the book reviews the special talent provisions for nearly four million students at 303 higher education institutions in eleven countries. In addition, it offers an analysis of the reasons to develop such programs, a look into the future of honors education and a practical list of suggestions for further research. The Sirius Program assigned Marca Wolfensberger to carry out this research.